Cells and Materials for Disease Modeling and Regenerative Medicine - Abarrategi, Ander; Lanceros-Mendez, Senentxu (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Materials science and engineering are strongly developing tools with increasing impact in the biotechnological and biomedical areas. Interestingly, research in molecular and cellular biology is often at the core of the design and development of materials-based approaches, providing biological rationale. Focused on research relying on biology-materials interaction, IJMS launched a Special Issue named "Cells and Materials for Disease Modeling and Regenerative Medicine". The aim of the Special Issue was to generate a compilation of in vitro and in vivo strategies based on cell-material interactions. This book compiles the papers published in that Special Issue and includes a selection of six original scientific experimental articles and six comprehensive reviews. We are convinced that this collection of articles shows representative examples of the state of the art in the field, unveiling the relevance of materials research in generating new regenerative medicine and disease modeling approaches.